2021
DOI: 10.1332/251510820x15978605298709
|View full text |Cite
|
Sign up to set email alerts
|

The subjective meaning of gender: how survey designs affect perceptions of femininity and masculinity

Abstract: The rationale for this study is that self-categorising rating scales are becoming increasingly popular in large-scale survey research moving beyond binary ways of measuring gender. We are referring here to the use of rating scales that are similar to graded scales capturing left–right or liberal–conservative political ideology, that is, scales that do not include predefinitions of the core concepts (femininity/masculinity, as compared to left/right or liberal/conservative). Yet, previous studies including such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The theoretical assumption of this study is that gendered thoughts, at least partly, may be driven by adherence to sociocultural norms for masculinity [ 3, 9, 10 ]. This assumption is supported by a recent study on perceptions of typical ‘masculine’ versus ‘feminine’ traits in Sweden which showed that masculinity, even in the Swedish context of gender equity, was linked to being agentic (decisive, competitive, focused) whereas femininity was linked to being communal (caring, relationship-oriented) [ 11 ]. A recent meta-analysis of US public opinion polls, covering more than 30,000 individuals, showed similar results and demonstrated that while some gender stereotypes changed over time –such as beliefs about individuals’ competence –beliefs about men as ambitious and courageous and women as affectionate and emotional were remarkably stable [ 12 ].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The theoretical assumption of this study is that gendered thoughts, at least partly, may be driven by adherence to sociocultural norms for masculinity [ 3, 9, 10 ]. This assumption is supported by a recent study on perceptions of typical ‘masculine’ versus ‘feminine’ traits in Sweden which showed that masculinity, even in the Swedish context of gender equity, was linked to being agentic (decisive, competitive, focused) whereas femininity was linked to being communal (caring, relationship-oriented) [ 11 ]. A recent meta-analysis of US public opinion polls, covering more than 30,000 individuals, showed similar results and demonstrated that while some gender stereotypes changed over time –such as beliefs about individuals’ competence –beliefs about men as ambitious and courageous and women as affectionate and emotional were remarkably stable [ 12 ].…”
Section: Introductionmentioning
confidence: 82%
“…Markstedt et al [ 11 ] showed that men and women in Sweden view themselves as having a mix of feminine and masculine characteristics. At the same time, more men than women scored high (many masculine traits) on a subjective masculinity scale and, vice versa, more women than men scored high (many feminine traits) on a subjective femininity scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in recent years, there has been growing critique of the binary approach to measuring gender (Bittner and Goodyear-Grant 2017; Hatemi et al 2012). Surveys using measures of sexual orientation and gender identity have recently come into use, but there is no consensus yet on how to introduce a nonbinary approach to quantitative methods (Markstedt et al 2021; Westbrook and Saperstein 2015).…”
Section: The Challenge That Multiple Identities Pose To Quantitative ...mentioning
confidence: 99%
“…Men’s higher likelihood of unmet need may be explained by gender norms in the society defining individuals’ possible actions and their consequences [ 17 – 19 ]. Dominant masculinity norms encourage men to be self-reliant, competitive, and decisive, and discourage feminine traits such as being weak, emotional, or shy [ 18 , 20 , 21 ]. This can lead to denial of symptoms and reluctance to seek healthcare, especially for depression and anxiety disorders that are traditionally connected to being feminine [ 18 , 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%